ChemInform Abstract: Catalytic Intermolecular Alkene Oxyamination with Nitrenes. Issue 3 (January 2015) - Dequirez, Geoffroy; Ciesielski, Jennifer; Retailleau, Pascal; Dauban, Philippe
Abstract The addition reaction of the nitrene, generated from the sulfonamide (II), to a variety of olefins in the presence of acetic acid is studied to provide an efficient oxyamination process with complete regioselectivity.